Effects of body size and root to shoot ratio on foliar nutrient resorption efficiency in Amaranthus mangostanus. Issue 3 (12th March 2019) - Peng, Huiyuan; Yan, Zhengbing; Chen, Yahan; Zhao, Xujian; Han, Wenxuan
Abstract : Premise of the Study: Nutrient resorption is essential for plant nutrient conservation. Large‐bodied plants potentially have large nutrient sink pools and high nutrient flux. Whether and how nutrient resorption can be regulated by plant size and biomass allocation are yet unknown. Methods: Using the herbaceous plant Amaranthus mangostanus in greenhouse experiments for two consecutive years, we measured plant biomass, height, and stem diameter and calculated the root to shoot biomass ratio (R/S ratio) and nutrient resorption efficiency (NuRE) to assess the effects of plant body size and biomass allocation on NuRE. NuRE was calculated as the percentage reduction in leaf nutrient concentration from green leaf to senesced leaf. Key Results: NuRE increased with plant biomass, height, and stem diameter, suggesting that the individuals with larger bodies, which led to a larger nutrient pool, tended to resorb proportionally more nutrients from the senescing leaves. NuRE decreased with increasing root to shoot ratio, which might have reflected the nutrient acquisition trade‐offs between resorption from the senescent leaves and absorption from the soil. Increased root biomass allocation increased the proportion of nutrient acquisition through absorption more than through resorption. Conclusions: This study presented the first experimental evidence of how NuRE is linked to plant size (indicated by biomass, height, and stem diameter) and biomass allocation, suggesting that nutrient acquisition could be modulated by the size of the nutrient sink pool and its partitioning in plants, which can improve our understanding of a conservation mechanism for plant nutrients. The body size and root to shoot ratio effects might also partly explain previous inconsistent reports on the relationships between environmental nutrient availability and NuRE.